9th Skin Academy Symposium: Building Bridges in Dermatology Chair's Introduction. Issue 1 (January 2017) - Blume-Peytavi, Ulrike
Abstract An introduction to the proceedings sharing an overview of presentations given as part of the 9th Skin Academy Symposium, held in Barcelona, Spain, April 9–10, 2016. The Skin Academy is an international and interdisciplinary dermatology initiative created to contribute to the growth in scientific knowledge of those dealing with skin diseases. This year's meeting aimed to 'build bridges' between the latest research and everyday clinical practice, providing dermatologists with important updates on some of the most common skin diseases, as well as current 'hot' topics.